MRI findings in juvenile Huntington's disease - Patrick Arraj, BS; Kyle Robbins, BS; Lauren Dengle Sanchez, MD; Daniel L. Veltkamp, MD; Cory M. Pfeifer, MD, MPH (Radiology Case Reports, 2021)
Juvenile Huntington's disease is a rare neurodegenerative disorder that first affects the basal ganglia. Presented here is a case of juvenile Huntington's disease in an 8-year-old male. Clinical features included epilepsy and developmental delay. Imaging findings showed severe atrophy of the caudate nuclei and putamina which prompted a genetic evaluation. The diagnosis was confirmed via molecular analysis which revealed the amplified CAG triplet characteristic of this disorder. This case report highlights the imaging features common in this rare cause of pediatric epilepsy.